INTENSIVE CARE OF THE PUERPERIUM (ICP) IMPACT ON THE POSTPARTUM SELF-CARE ABILITY IN WONOKROMO - Yunik Windarti; Yunik Windarti; Uke Maharani Dewi; Uke Maharani Dewi (Siklus : Journal Research Midwifery Politeknik Tegal, 2020)
Health monitoring since pregnancy to puerperium is crucial to do to avoid complications. Monitoring during the puerperium period still lacked, especially when the mother has returned home. Many complications occur during the puerperium, such as healing of perineal tears, uterine subinvolution, psychological factors, breastfeeding problems (blocked duct, engorgement, mastitis), and not few found death due to bleeding and infection. Special attention and debriefing for postpartum mothers were needed to prepare mothers to be more independent in caring for themselves. The purpose of this study was to analyze intensive care of the puerperium (ICP) effect on postpartum self-care capability. Method of this study was Quasi-experimental research with a quantitative study combination approach (experimental group) on ICP and qualitative methods (interviews) on postpartum self-care. The population of this study were postpartum maternal taken as the sample using nonprobability sampling technique with incidental sampling for three months in Wonokromo Sub-district, Surabaya. The data were analyzed using the chi-square test. The results showed from 37 respondents who received ICP, 62.16% of respondents were able to carry out postpartum self-care properly. Furthermore, from 37 respondents who did not receive ICP, 70.27% of respondents found lacking to carry out postpartum self-care. The p-value = 0.005 p = 0.05 means that there was an influence of ICP on postpartum self-care ability.Keywords: Intensive care of the puerperium, Self-care